Total synthesis and biological activity of “carbamorphine”: O-to-CH 2 replacement in the E-ring of the morphine core structure - Sota Akiyama; Rohini S. Ople; Alexander Kremsmair; Nokomis Ramos-Gonzalez; Thomas Nedungadan; Brandon J. Kennedy; Kevin Appourchaux; Shainnel O. Eans; Bowen A. Tsai; Christina Kraml; Xi-Ping Huang; Jay P. McLaughlin; et al. (Proceedings of the National Academy of Sciences, 2025)
Morphine is a µ-opioid receptor (MOR) agonist and potent analgesic. However, it displays several side effects including respiratory depression and addiction. Here, we show that a single heavy atom replacement in the morphine core structure (O to CH 2 exchange in the E-ring) prepared through a 15-step total synthesis displays a different pharmacological profile. The total synthesis features an intramolecular inverse electron-demand Diels−Alder cycloaddition and a stereoselective Giese radical addition to construct a quaternary carbon center. Unlike morphine, where the (–)-morphine enantiomer binds the MOR, both enantiomers of this “carba” variant, which we have named carbamorphine, possess activity as agonists of the MOR. Cell-based functional assays show that (+)-carbamorphine shows reduced G-protein as well as β-arrestin efficacy at the MOR. In mouse behavioral assays, (+)-carbamorphine exhibits MOR-selective antinociception while showing reduced respiratory depression and a lack of conditioned place preference at supratherapeutic doses. Overall, through a net “single-atom” change (i.e., O to CH 2 ) in the morphine framework, different pharmacological profiles have been realized. This work provides a basis for additional syntheses and the study of morphine analogs that incorporate atom changes in the core framework.